How trade participation fuels innovation in Africa: Unveiling insights through empirical analysis - Ijirshar Victor Ushahemba; Okpe Isa Jibrin; Andohol Jerome Terhemba (Ekonomski Anali)
By utilising a nonstationary heterogeneous approach to uncover the dynamics between foreign trade participation and innovation levels in developing economies, this empirical study investigates how trade participation fuels innovation in 25 selected African countries. The African continent is experiencing significant economic growth and globalisation, making it essential to understand the potential linkages between international trade and innovation. Using a dynamic fixed effect estimator within the framework of nonstationary heterogeneous panel models on panel data of 25 African countries from 1996 to 2021, the study revealed that national income significantly influences both exports and imports in the region. The study also identified bidirectional causal links between industrial design applications, patents, and trademarks with exports and imports, highlighting the symbiotic relationship between innovation and trade engagement. Successful exports are found to foster investments in design, patents, and branding. Recommendations on the basis of these findings include fostering innovation ecosystems through research institutes and collaborations, developing balanced trade policies to support domestic industries and SMEs, offering incentives for research and development, and strengthening trade promotion agencies to assist businesses in navigating international markets, identifying trade opportunities, and addressing export-import challenges.